Language Acquisition (Types of Sentence) of Three to Four Years Old Children - Wenny Aulia Sari; Tri Dina Ariyanti (IAIN Bengkulu, 2022)
This study discussed the language acquisition of children aged 3-4 years. In general, children aged three to four years are able to produce various types of sentences to communicate their goals to others. This study aimed to describe what types of sentences are acquired by children aged three to four years. This type of research was qualitative research using the descriptive method. The collection of data in this research utilized recording and note-taking techniques. The data analysis technique used in this study consisted of data reduction, data presentation, and conclusion drawing. The results of this study indicated that all types of sentences in the form of declarative sentences, interrogative sentences, imperative, and exclamatory sentences can be said by children aged three to four years. Sentences that are often said by children aged three to four years are news sentences (declarative).